INTERNAL MODIFICATION IN REQUESTING USED BY EFL LEARNERS - Khairunnisa Khairunnisa (Universitas Pendidikan Mandalika, 2014)
Speech acts realization of request is distinct for it leaves benefit to the requester but loss to the requestee. Thus, politeness is a primary issue in requesting. Therefore, internal modification can be used to soften the impact of the request. This paper looks into the internal modification used by EFL learners compared to the native speakers. Discourse Completion Tasks (DCT) is used to obtain the data. Then, the internal modification strategy is analyzed based on Trosborg's strategy of request (Trosborg, 1994). The research reveals the variety of the internal modification used by EFL learners are still limited compared to the native speakers. In this case, some factors are proved to determine the performance of the strategy being used such as proficiency and direct contact with native speakers as well as immersion in the English exposure, e.g length of stay in English speaking country.